Characteristics and risk factors for medical malpractice among obstetric and gynecologic physicians in China - Shuwen Zhang; Lei Li; Fangfang Wang; Hongyan Wang; Kan Wang; Xiaomin Zhang; Yang Cao; Congcong Ma; Guohong Li; Lan Zhu (BMC Health Services Research)
Abstract Background Limited information is available on malpractice claims against obstetricians and gynecologists in China. This study identifies risk factors associated with malpractice and explores the correlation between the hospital characteristics and medical errors in obstetrics and gynecology. Methods This observational study analyzed all obstetric and gynecologic malpractice claims submitted to the Chinese Medical Association (CMA) from 2016 to 2023. Data were extracted from the CMA appraisal reports, including hospital type (general or specialized), tier (primary, secondary, or tertiary), ownership (public or private), primary department involved (obstetrics or gynecology), and detailed case characteristics. Malpractice claims were categorized by the type of medical error. Univariate and multivariate analyses were conducted to assess associations between medical errors and personal, administrative, and professional factors. Results Among the 3,719 cases evaluated by the CMA, 3,676 were confirmed as malpractice. Nonfatal disability occurred in 1,339 cases (36.4%), and death occurred in 735 cases (20.0%). Specialized hospitals had a lower risk of malpractice-related death compared with general hospitals (odds ratio [OR] = 0.785; 95% confidence interval [CI] = 0.637–0.967). Private hospitals showed a reduced risk of severe nonfatal disability compared to public hospitals (OR 0.572; 95% CI 0.361–0.907). Secondary and tertiary hospitals were associated with a higher risk of severe nonfatal disability (OR 1.698 and 1.835, respectively; 95% CI 1.084–2.658 and 1.121–3.004) but a lower risk of primary liability compared with primary hospitals (OR 0.783 and 0.527; 95% CI 0.635–0.965 and 0.419–0.664). Compared with gynecology departments, obstetric cases presented a higher risk of malpractice-related death (2.866; 2.347–3.501) but a lower risk of primary liability (0.643; 0.559–0.740). Compared with public hospitals, private hospitals had more credential-related errors but fewer issues with informed consent and documentation. Obstetric cases more often involved errors in procedural timing, monitoring, and evaluation, whereas gynecologic cases had a higher frequency of surgical process errors (all P < 0.001). Conclusions This study provides the first nationwide analysis of obstetric and gynecologic malpractice claims in China. Strengthening grassroots and private hospitals and refining the hierarchical medical system may improve patient safety and healthcare sustainability. Trial registration Not available.